2008
DOI: 10.1093/eurheartj/ehp048
|View full text |Cite
|
Sign up to set email alerts
|

One-year results of total arterial revascularization vs. conventional coronary surgery: CARRPO trial

Abstract: Within 1 year post-operatively, TAR seems at least as safe and effective as CR. Prolonged follow-up will reveal whether this is sustained or superior results of TAR can justify a more general use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Our 1-year results of more robust outcome measures (graft patency and cardiac event-free survival) showing no differences between groups, support this. 7 Conversely, our trial was underpowered to detect small but potentially existing relevant differences (5-10 points) in SF-36 scores. 10 This is also the case for reporting of complications related to conduit harvest.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our 1-year results of more robust outcome measures (graft patency and cardiac event-free survival) showing no differences between groups, support this. 7 Conversely, our trial was underpowered to detect small but potentially existing relevant differences (5-10 points) in SF-36 scores. 10 This is also the case for reporting of complications related to conduit harvest.…”
Section: Discussionmentioning
confidence: 96%
“…We have found comparable outcomes for both groups after 1 year regarding graft patency and cardiac event-free survival. 7 This article deals with the results of preoperative and postoperative measurements of HRQoL at 3 and 11 months using the generic questionnaire Short Form-36 (SF-36).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, there have been few randomized controlled trials comparing MAG with LIMA grafts/SVGs or conventional grafting [25][26][27]35]. A series of trials from Muneretto et al enrolled between 176 and 200 patients to undergo CABG surgery with MAG (exclusive arterial grafting) compared with LIMA grafts/SVGs.…”
Section: Perspectivementioning
confidence: 99%
“…However, at follow-up of 12-16 months, the rates of angina recurrence, percutaneous coronary intervention (PCI) and event-free survival appeared significantly lower in the MAG group [25][26][27]. A more recently published trial in which 331 patients were randomized between MAG and conventional grafting was unable to demonstrate any significant outcome differences at 1-year follow-up [35]. In this particular study, one should note that fewer than 47% of patients in the MAG group received BIMA, and that some of the radial arteries used were placed to moderately stenosed vessels, perhaps accounting for their findings [35].…”
Section: Perspectivementioning
confidence: 99%
“…The 1-year results for total arterial revascularization, in which the RA was used as a composite or aortocoronary conduit in addition to in-situ bilateral ITA grafting, vs conventional coronary CABG (CARRPO trial) showed similar graft patency, and cardiacevent-free rates at 1 year after CABG. 76 …”
Section: Randomized Controlled Trialsmentioning
confidence: 99%